Perencanaan dan Pengendalian Proyek dengan Metode CPM (Critical Path Method) di PT Ghani Sejahtera Abadi - Nur'aini Muhassanah; Ikhsani Annisa Khozinati (Scientific Timeline, 2021)
The purpose of this study is to apply the CPM (Critical Path Method) method to predict and optimize the project's total duration on the scheduling of house construction projects by PT Ghani Sejahtera Abadi. In this research, the method used is quantitative with a descriptive approach. The subjects of this research are project owners and workers who build houses in Kedungrandu Regency Housing. Sources of data needed to meet the criteria for data that CPM can analyze include: (a) data on the name of the activities in the project, (b) the sequence of activities on the project, and (c) data at the time used in the house construction project. For data collection in this study using several techniques, namely interviews and literature study. Based on the results and discussion of this research, the following conclusions are obtained: (1) Critical Path Method (CPM) can be used to schedule optimal, fast, and efficient house construction projects. (2) The CPM application causes the completion time of the type 33 house construction project in the Kedungrandu Regency Housing, which was initially scheduled for 64 days to be faster, namely 42 days.